Lacunary difference sequences of complex uncertain variables - Dowari, P. J.; Tripathy, B. Ch. (Methods of Functional Analysis and Topology, 2020)
Using the concept of difference operator on sequence spaces and uncertainty theory, some new class of lacunary convergent difference sequences of complex uncertain variables have been introduced for the lacunary convergence. Some topological properties of the defined sequence spaces along with the inclusion relations have been investigated. Користуючись поняттям різницевого оператора на просторі послідовностей і теорією невизначеності, ми досліджуємо клас лакунарно збіжних різницевих послідовностей комплексних невизначених змінних. Розглядаються топологічні властивості введених просторів послідовностей, а також їхні вкладення.